Malay idiomatic expressions: Their structure and categorization - Tajuddin, Norafidah (Journal of Modern Languages, 2017)
Most people believe that they have mastered a language when they are able to express themselves fluently in it. But language is not just about words and grammar; language is unique because it reflects the culture of the people using it. Hence to be able to master a language and understand the actual meaning behind the words, expressions and sentences uttered, one needs to learn the language frills such as idiomatic expressions and colloquial forms. Expressions like 'to read him like a book', 'on the house', 'to be nuts' and 'like a house on fire , may not be understood correctly by a non-native speaker of English if he were to interpret the meaning literally.